Incidence of infection in Wearing Contact Lenses during Covid-19: A Scoping Review - Shinta Restu Wibawa (Fakultas Ilmu Kesehatan, 2021)
During the Covid-19 pandemic, many people reduced their use of contact lenses because of eye infections, but also many people continued to use them. The electronic database scoping review for studies related to Incidence of infection in wearing contact lenses during covid-19.This study followed the acronym PCC (P = population; C = concept; C = context). Papers related to the topic were selected based on their source and publication titles so that 5 papers were obtained. From the five papers, it was found that the incidence of eye infections due to using contact lenses in the pandemic era was very small and low. Some of these studies explained that infections caused, for example, redness and other symptoms of infection, were not solely due to the transmission of the Covid-19 virus, but due to other factors such as the lack of attention of contact lens users on hygiene. It was found that the incidence of eye infections due to using contact lenses in the pandemic era was very small and low